Sosialisasi Bahaya Narkoba di Desa Mojodowo Kecamatan Kemlagi - Harjo Lukito; Gilang Mahendra; Ananda Tiara Salsabila; Ivan Budi Suryono; Hafid Ainul Yakin; Afif Fianda Rehza; Mohamad Suudi; Ardhoni Redho Pratama; Rhobiahtus Sholikhah; Kharisma Nadya Sefty Az-Zahra; Uswatun Khasanah; Irgi Nabil Maulidina; Iva Nurfitriyah; Dewi Aamalia Putri; Sherly Vijayanti; Magdalena Yunanda Wiranatha; Sayyid Naj’muddin; Muchammad Muzzaki Ma’ruf; Amalisa Marta Sari; Novi Anggrainy; Salisa Taskiya Fara; Annisa Amalia Rosyida; Paiman Paiman; Bella Ayu Wulandari (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
Drug abuse has become one of the most alarming social issues in Indonesia, particularly among the younger generation. This community service activity aims to enhance public awareness and understanding of the dangers of drug abuse through a socialization program conducted in Mojodowo Village, Kemlagi District, Mojokerto Regency. The methods employed include lectures, interactive discussions, and evaluations in the form of pre-tests and post-tests. The socialization materials cover the definition of drugs, their impact on health and society, and preventive measures that can be taken by the community. The results indicate a significant improvement in participants' understanding of drugs and the importance of preventing their misuse. This program positively influenced participants, especially the youth, by fostering collective awareness of the dangers of drug abuse and emphasizing the critical role of the community in creating a drug-free environment.